Lysozyme activity as an indicator of innate immunity of tilapia (Oreochromis niloticus) when challenged with LPS and Streptococcus agalactiae - Biller, Jaqueline Dalbello [UNESP]; Polycarpo, Gustavo Do Valle [UNESP]; Moromizato, Basia Schlichting [UNESP]; Sidekerskis, Ana Paula Diogo [UNESP]; da Silva, Thaís Daltoso [UNESP]; Reis, Ingrid Camargo Dos [UNESP]; Fierro-Castro, Camino (Revista Brasileira de Zootecnia, 2021)
The objective of this study was to fully describe the protocol with standardized modifications and evaluate the lysozyme activity, an indicator of innate immunity in tilapia, to compare lipopolysaccharide (LPS) with Streptococcus agalactiae injections. Lysozyme was determined in serum using the turbidimetric method, in which lysozyme activity was evaluated by Micrococcus lysodeikticus lysis, with modifications for microplate assay. The experiment was conducted in a completely randomized design. Juvenile tilapia was divided in the following six treatments: challenged with phosphate buffer PBS (control) and 100, 250, 500, and 600 pg kg-1 LPS and S. agalactiae. All treatments were challenged for 72 h and seven days and then sampled to determine lysozyme activity. After 72 h or seven days, concentrations of LPS promoted changes in lysozyme production, either lesser or equal, depending on concentration when compared with fish injected with S. agalactiae. It was possible to standardize the analysis and determine that the treatment with LPS promotes immunomodulation at a concentration of 250 pg kg-1 LPS, this response being similar to challenge with S. agalactiae.
Keywords: aquaculture; cell wall; enzyme; fish; immune response